Perkembangan Ilmu Pengetahuan di masa Dinasti Umayyah (41-132 H/661-750 M) - Nurhasan Nurhasan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
The Omayyad Dynasty is not only well known by its military power but also its development of science, such as Al-Qur'an studies (ulum al-Qur'an), language, history, islamic law (fiqh), Hadis, literature. medical. and chemistry